(untitled) (Medical Forum Monthly, 2024)
Objective: To find the antioxidant activity of Picrorhiza Kurroa(Pk) in liver against nimesulide induced oxidative stress. Study Design: Experimental animal study on mice Place and Duration of Study: This study was conducted at the National Institute of Health, Islamadad from Feb 2013 to March 2014. Materials and Methods: Heapatotoxicity was induced in mice by giving 750 mg/kg body weight of nimesulide foe 3 days and for establishing hepatoprotective activity, Picrorhiza kurroa was given for 14 days in two doses of 250 mg/kg and 500 mg/kg. Liver function analysis was carried out and serum glutathione peroxidase levels were measured to assess the antioxidant role of Picrorhiza Kurroain liver. Results: Our study showed significant results for serum bilirubin and alanine aminotransferase (ALT) in mice receiving the two doses of Picrorhiza Kurroa. Similarly significant result was seen in serum glutathione peroxidase (GPx) showing Pk as a potent antioxidant against nimesulide toxicity. Conclusion: This study demonstrated Pk as a strong antioxidant against nimesulide induced hepatic damage and the mechanism of hepatoprotection is by production of free radicals.